Age‐ and sex‐related changes in rat renal function and pathology following neonatal hyperoxia exposure. Issue 15 (15th August 2016) - Sutherland, Megan R.; Béland, Chanel; Lukaszewski, Marie‐Amélie; Cloutier, Anik; Bertagnolli, Mariane; Nuyt, Anne Monique
Abstract: Preterm neonates are prematurely exposed to high oxygen levels at birth which may adversely impact ongoing renal development. The aim of this study was to determine the effects of neonatal hyperoxia exposure on renal function and morphology with aging. Sprague Dawley rat pups were raised in a hyperoxic environment (80% oxygen) from P3 to P10 during ongoing postnatal nephrogenesis. Control litters were kept in room air ( n = 6–8 litters/group; one male, one female/litter/age). Kidney function (urine and plasma creatinine, sodium, and protein) and morphology (renal corpuscle size, glomerulosclerosis, fibrosis, and glomerular crescents) were assessed at 1, 5, and 11 months of age. Neonatal hyperoxia exposure had no impact on body or kidney weights. Creatinine clearance was significantly reduced following hyperoxia exposure at 5 months; there was no significant effect on renal function at 1 or 11 months. The percentage of crescentic glomeruli (indicative of glomerular injury) was markedly increased in 11 month hyperoxia‐exposed males. Renal corpuscle size, glomerulosclerosis index, and renal fibrosis were not affected. Findings suggest that exposure to high oxygen levels during development may impact renal functional capacity and increase susceptibility to renal disease in adulthood depending on age and sex. Abstract : Preterm neonates are prematurely exposed to high oxygen levels at birth which may adversely impact ongoing renal development. In a rat model of neonatal hyperoxia exposure, animals exhibited impaired renal functional capacity and an increased susceptibility to renal disease (glomerular crescents) in adulthood, with findings dependent on age and sex.